Antecedents to Thai pre-service teacher eco-friendly behavior: A confirmatory factor analysis - Pimdee, Paitoon; Meekhobtong, Sirinthorn; Bengthong, Suwanna; Sukkamart, Aukkapong (My University, 2022)
The research aimed to analyze the eco-friendly behavior (EFB) of Thai undergraduate pre-service teachers (PSTs). Multi-stage random sampling was used to select 211 individuals majoring in industrial education from four Thai universities. The second-order confirmatory factor analysis used LISREL 9.10 and SPSS for Windows 21 was used for the descriptive statistics. Furthermore, five elements were perceived to influence PST EFB positively. This included the product's eco-friendly price (EFP), eco-friendly safety (EFS), eco-friendly image (EFI), eco-friendly environment (EFE), and finally eco-friendly quality (EFQ). Moreover, it was determined that a product's EFI was most important to the PSTs, followed by its EFQ, EFS, EFE, and EFP. Moreover, of the 20 items the PSTs were asked about, they believed that non-plastic bag use for EFB was judged most important. However, at the other end of EFB was a product's price importance.
Keywords: environmental product awareness; environmental sustainability; perceived behavior; student-teachers; Thailand